Neuroprotective effect of α-mangostin on mitochondrial dysfunction and α-synuclein aggregation in rotenone-induced model of Parkinson's disease in differentiated SH-SY5Y cells. Issue 8 (3rd August 2017) - Hao, Xin-Mei; Li, Lian-Da; Duan, Chang-Ling; Li, Yu-Juan
Abstract: The study was designed to evaluate the protective effect of α-mangostin and explore its mechanism in an in vitro model of Parkinson's disease (PD) induced by rotenone. SH-SY5Y cells were treated with rotenone and α-mangostin for 24 h. α-Mangostin significantly and concentration-dependently inhibited rotenone-induced cytotoxicity. The rotenone-induced aggregation of α-synuclein and loss of TH were alleviated by α-mangostin. α-Mangostin treatment also reversed the rotenone-induced overproduction of reactive oxygen species, activation of caspases (−8 and −3) and mitochondrial dysfunction, reflected by decrease in mitochondrial membrane potential and cellular ATP levels. These findings suggest that α-mangostin has neuroprotective effects against PD-related neuronal injury. Abstract :